2017
DOI: 10.3748/wjg.v23.i36.6628
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroid therapy in inflammatory bowel diseases: From clinical practice to molecular biology

Abstract: Inflammatory bowel diseases (IBDs), such as ulcerative colitis and Crohn’s disease, are chronic pathologies associated with a deregulated immune response in the intestinal mucosa, and they are triggered by environmental factors in genetically susceptible individuals. Exogenous glucocorticoids (GCs) are widely used as anti-inflammatory therapy in IBDs. In the past, patients with moderate or severe states of inflammation received GCs as a first line therapy with an important effectiveness in terms of reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 92 publications
1
74
0
4
Order By: Relevance
“…Based on published data, we chose 10 SNPs reported to affect GC e cacy in patients with various diseases: rs17209237, rs11745958, rs33388, rs7701443, rs41423247, rs6189, rs6190, rs6195, rs6196, and rs6198 [10], [11], [12], [13], [14], [15], [16], [17]. Whole blood samples from all patients were collected in tubes containing ethylenediamine tetra-acetic acid (EDTA) and sent to our Biotechnology Center for TaqMan SNP genotyping [18].…”
Section: Nr3c1 Snp Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on published data, we chose 10 SNPs reported to affect GC e cacy in patients with various diseases: rs17209237, rs11745958, rs33388, rs7701443, rs41423247, rs6189, rs6190, rs6195, rs6196, and rs6198 [10], [11], [12], [13], [14], [15], [16], [17]. Whole blood samples from all patients were collected in tubes containing ethylenediamine tetra-acetic acid (EDTA) and sent to our Biotechnology Center for TaqMan SNP genotyping [18].…”
Section: Nr3c1 Snp Genotypingmentioning
confidence: 99%
“…GCs exert their biological effects via GC receptor (GR), which regulates the expression of GC-target genes [8], [9]. Earlier studies reported that several NR3C1 single nucleotide polymorphisms (SNPs) (rs6189, rs6190, rs6195, rs6196, rs6198, and rs41423247) might correlate with GC e cacy in patients with in ammatory bowel disease, rheumatoid arthritis, asthma, and idiopathic nephrotic syndrome [10], [11], [12], [13], [14], [15], [16]. For PV patients, Fang et al [17] were the rst to report associations between NR3C1 SNPs and GC e cacy; rs11745958 C/T and rs17209237 A/G may be associated with increased risks of GC resistance, but rs33388 A/T and rs7701443 A/G with decreased risks.…”
Section: Introductionmentioning
confidence: 99%
“…Associations with cellular proliferation and antiinflammatory responses (47) Exogenous glucocorticoids are heavily used as antiinflammatory therapy for IBD (48,49)) ATG16L1, an autophagy related gene, was downregulated in patients who do not respond to glucocorticoid treatment (50,51) Transcriptionally regulates NFKβ1, a SNP affected gene in ulcerative colitis (52,53) VDR (Vitamin D Receptor)…”
Section: Nr3c1 (Glucocorticoid Receptor)mentioning
confidence: 99%
“…Among these pathways, both steroid metabolism and biosynthesis were found to be associated with IBD. Steroids are a well-known and commonly utilized treatment for patients with active Crohn's disease (52). Enrichment in steroid metabolism in the gut microbiome could be reflective of an increase in steroid availability due to treatment.…”
Section: Implications For Ibdmentioning
confidence: 99%